Early Neuro-Psychomotor Therapy Intervention for Theory of Mind and Emotion Recognition in Neurodevelopmental Disorders: A Pilot Study - Elisa Giangiacomo; Maria Castellano Visaggi; Franca Aceti; Nicoletta Giacchetti; Melania Martucci; Federica Giovannone; Donatella Valente; Giovanni Galeoto; Marco Tofani; Carla Sogos (Children, 2022)
The aim of the present study is to explore the effect of early neuro-psychomotor therapy to improve theory of mind skills and emotion recognition in children with neurodevelopmental disorders. A pilot study was set up, consisting of in-group training activities based on the neuro-psychomotor approach. Children were evaluated using Neuropsychological Assessment for Child (Nepsy-II), Test of Emotion Comprehension (TEC), and Social Communication Questionnaire (SCQ). For data analysis, one-sample Wilcoxon signed rank test was used with a significance of p < 0.05. Two children with a developmental language disorder and four children with autism spectrum disorders participated in a 3-month training program. Our findings revealed significant improvement in emotion recognition, as measured with Nepsy-II (p = 0.04), while no statistical improvement was found for theory of mind. Despite the limited sample, early neuro-psychomotor therapy improves emotion recognition skills in children with neurodevelopmental disorders. However, considering the explorative nature of the study, findings should be interpreted with caution.